2019
DOI: 10.1093/cercor/bhz083
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Connectivity and Cortical Maturation Are Promoted by the ω-3 Fatty Acid Docosahexaenoic Acid

Abstract: Brain development is likely impacted by micronutrients. This is supported by the effects of the ω-3 fatty acid docosahexaenoic acid (DHA) during early neuronal differentiation, when it increases neurite growth. Aiming to delineate DHA roles in postnatal stages, we selected the visual cortex due to its stereotypic maturation. Immunohistochemistry showed that young mice that received dietary DHA from birth exhibited more abundant presynaptic and postsynaptic specializations. DHA also increased density and size o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 98 publications
2
12
0
Order By: Relevance
“…These results are in line with previous data showing positive effects of Omega 3 fatty acids on dendritic arborization and new spine formation in the hippocampus during normal ageing 45,46 and on neurite length and branching in hippocampal embryonic neuronal cell cultures 47,48 . Interestingly, previous literature has demonstrated the link between enhanced neuronal dendritic growth in the motor cortex with motor functional improvements 49 .…”
Section: Neurodevelopmental Effects Of the Perinatal Administration Osupporting
confidence: 93%
“…These results are in line with previous data showing positive effects of Omega 3 fatty acids on dendritic arborization and new spine formation in the hippocampus during normal ageing 45,46 and on neurite length and branching in hippocampal embryonic neuronal cell cultures 47,48 . Interestingly, previous literature has demonstrated the link between enhanced neuronal dendritic growth in the motor cortex with motor functional improvements 49 .…”
Section: Neurodevelopmental Effects Of the Perinatal Administration Osupporting
confidence: 93%
“…Unesterified DHA Regulates Synapse/Spine Density In Vivo through RXRA Long-term DHA deprivation (in weeks or months) in vivo has been shown to impair synapse function and cognition-related performance, while long-term DHA supplementation improved both parameters (Carbone et al, 2020;de la Presa Owens and Innis, 1999;Igarashi et al, 2011;Lafourcade et al, 2011;Nguyen et al, 2014;Ramakrishnan et al, 2009). However, the mechanism by which DHA regulates synapse function and/or cognition-related performance remains largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanism by which DHA regulates synapse function and/or cognition-related performance remains largely unknown. In vitro administration of unesterified DHA promoted synapse development on the timescale of hours to days (Cao et al, 2009;Carbone et al, 2020;Fujita et al, 2001;Mazzocchi-Jones, 2015). Why does it take so long?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…85 Since it accumulates in the brain mainly during the last trimester of pregnancy, 86 preterm birth is associated with early deficits in cortical DHA. 85 Animal studies have shown that dietary supplementation from birth with DHA alone or in mixture with eicosapentaenoic acid promotes synaptic connectivity and cortical processing, 87 and also protects the neonatal brain against hypoxic/ischemic injury. 88 Supplementation during pregnancy was also shown to protect against lipopolysaccharide (LPS)-induced white matter injury in the neonatal rat brain.…”
Section: Dietary Supplementsmentioning
confidence: 99%